5x+48+7x=12(x-4)

Simple and best practice solution for 5x+48+7x=12(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+48+7x=12(x-4) equation:


Simplifying
5x + 48 + 7x = 12(x + -4)

Reorder the terms:
48 + 5x + 7x = 12(x + -4)

Combine like terms: 5x + 7x = 12x
48 + 12x = 12(x + -4)

Reorder the terms:
48 + 12x = 12(-4 + x)
48 + 12x = (-4 * 12 + x * 12)
48 + 12x = (-48 + 12x)

Add '-12x' to each side of the equation.
48 + 12x + -12x = -48 + 12x + -12x

Combine like terms: 12x + -12x = 0
48 + 0 = -48 + 12x + -12x
48 = -48 + 12x + -12x

Combine like terms: 12x + -12x = 0
48 = -48 + 0
48 = -48

Solving
48 = -48

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| y^2-10y+25=3-x | | (9x+2)(3x^2-20x-7)=0 | | y=-2x^2-2x-3 | | 9x-32=9x-33 | | -2=8x | | 39=3(2x-1) | | 15-(-11)= | | 5(2b+1)=25 | | 8b-1=3 | | 7a-6-6a=3+1 | | -54+18= | | 6(-5)= | | 32=3y-7 | | r+16=5r+10 | | 2+t=27-4T | | 3v^2+23v+40=0 | | 6(x+y)+(x-y)= | | 8x+25=3x+145 | | 7-2(m+1)= | | 107-2x=34x+15 | | 8-8x=58-43x | | (2x+3)-1=6 | | 4x-39=647 | | y=4E+07 | | x+38+4x-39=857 | | 3x^2=-4x-1 | | 2v=8 | | 4x^2-144= | | 2x+11x=65+x | | 6x^2-54= | | 25x^2+10x+1= | | 84-3x=15x+16 |

Equations solver categories